2012
DOI: 10.1002/hipo.22031
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive demands induce selective hippocampal reorganization: Arc expression in a place and response task

Abstract: Place cells in the hippocampus can maintain multiple representations of a single environment and respond to physical and/or trajectory changes by remapping. Within the hippocampus there are anatomical, electrophysiological, and behavioral dissociations between the dorsal and ventral hippocampus and within dorsal CA1. Arc expression was used to measure the recruitment of ensembles across different hippocampal subregions in rats trained to utilize two different cognitive strategies while traversing an identical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 79 publications
3
20
1
Order By: Relevance
“…The findings of the current research highlight the importance of controlling for locomotor indices when attempting to relate theta indices to cognitive operations [12], [40][41], particularly in experimental paradigms that involve manipulations (e.g., behavioral choices, pharmacologic), sensorimotor variables and correlated changes in theta spectral indices. The present findings demonstrate predictable changes in theta LFP signals in relation to acceleration and deceleration and how that relationship changes along the septotemporal axis of the HPC.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The findings of the current research highlight the importance of controlling for locomotor indices when attempting to relate theta indices to cognitive operations [12], [40][41], particularly in experimental paradigms that involve manipulations (e.g., behavioral choices, pharmacologic), sensorimotor variables and correlated changes in theta spectral indices. The present findings demonstrate predictable changes in theta LFP signals in relation to acceleration and deceleration and how that relationship changes along the septotemporal axis of the HPC.…”
Section: Discussionmentioning
confidence: 91%
“…The increase in theta power as a function of running speed has been confirmed in subsequent studies [37][39], but recently has been shown to vary systematically across the long axis of the HPC [28], [30]. Most rodent studies examining the relationship between cognitive performance and theta involve spatial locomotion often along relatively fixed trajectories [12], [40][41] and can involve deceleration when animals are within regions of “choice” (often turns). Thus, a better understanding of the relative contribution of speed and acceleration to changes in theta should facilitate our understanding of how variations in theta relate to sensorimotor and/or cognitive processes.…”
Section: Introductionmentioning
confidence: 89%
“…These results are also interesting to consider with respect to the findings of Schmidt et al (2012). The authors visualized Arc expression to compare population activity between distal and proximal CA1 while rats found reward in a radial arm maze using two different cognitive strategies.…”
Section: Discussionmentioning
confidence: 95%
“…However, global remapping in the DG is not just observed during discrimination of contextual representations, instead resolving conflicting goals also engenders global remapping in the DG (Satvat et al, 2011;Schmidt et al, 2012b). Thus, pattern separation in the DG-CA3 circuit may constrain the overgeneralization of fear in ambiguous threatening contexts or when threat is uncertain.…”
Section: Studies Examining the Role Of Dg In Resolving Interference Amentioning
confidence: 91%